Corporate Social Responsibility and Firm Value with Profitability, Firm Size, Managerial Ownership, and Board of Commissioners as Moderating Variables - Sugiyanto, Eko; Trisnawati, Rina; Kusumawati, Eny (Universitas Muhammadiyah Surakarta, 2021)
The purpose of this study was to analyze the influence of CSR on firm value with profitability, firm size, managerial ownership, and board of commissioners as moderating variables. This study’s population was manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2014-2018 period. The sample was determined by purposive sampling technique and obtained a sample of 154 companies. This research employed statistical analysis by regression analysis with moderating variables. This study’s results revealed that corporate social responsibility affected firm value. Company profitability and size could moderate the relationship between CSR and firm value. Meanwhile, managerial ownership and the board of commissioners could not moderate the relationship between CSR and firm value.